Női-férfi szerepek a koedukációs oktatás tükrében Sárospatakon a 19. században - BÁTHORINÉ MISÁK, Marianna (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2016)
Male and Female Roles in the Perspective of Coeducation in Sárospatak in the 19th Century. For a long time, the possibility of education of women was determined by public opinion, meaning especially that of men. With respect to their different roles, according to the dominant beliefs, women should stick to the old, traditional tasks and roles inherited from antiquity, not wanting anything more. Obviously – as discussed – this kind of perception could not survive for long. Women did not want to take over the role of the stronger sex, but to be educated in order to perform their tasks better and to fulfil their roles with more quality. After all, only an educated person can educate others. How would they educate intelligent, resourceful men for the country, if they themselves could not share in the opportunities provided by education? That is why a lot of efforts were made which eventually paved the way to the opportunities available today. By now, perhaps we have fallen on the other extreme. From time to time, the over-emphasis of emancipation – in our understanding – is an excuse for not fulfilling one’s real roles. As a consequence, the true values and roles which both sexes should fulfil have been far removed from what is normal. A working mother asserting her interest to work is just unable to qualify for the role, next to all other ones, which is the finest one in the world, to truly be a mother. The image of the man holding the role of the breadwinner became so diverse. The alcoholic, aggressive or even workaholic dads are not drawing the ideal father figure of themselves. But all this may not fall within the framework of our topic; it is just mentioned because today’s education has led to the blurring and distorting of roles.